Development of Alkaline Fuel Cells Using Hydroxide-Ion Conductive Layered Double Hydroxides. (14th September 2015) - Tadanaga, Kiyoharu; Igarashi, Kohei; Kubota, Takashi; Miura, Akira; Higuchi, Mikio
Abstract : Layered double hydroxides (LDHs) intercalated with CO3 2- show high hydroxide ion conductivity of the order of 10 -3 S cm -1 under 80% relative humidity. In the present study, (Ni, Mn)-Al LDHs and (Ni, Mn)-Fe LDHs intercalated with CO3 2- were prepared. The conductivity of (Ni, Mn)-Al LDH and (Ni, Mn)-Fe LDH was higher than that of Ni-Al LDH or Ni-Fe LDH. These LDHs were applied to the catalyst layer in an alkaline fuel cell for the improvement of the oxygen reduction reaction (ORR) at the triple phase boundary (TPB) in the catalyst layer. The addition of LDHs to the catalyst layer increased the current for ORR, indicating that hydroxide ion conducting LDHs introduced OH - conducting paths and increased TPB region within the catalyst layer. Above all, the addition of (Ni, Mn)-Fe LDH to the catalyst layer more effectively increased the reduction current for ORR than the addition of (Ni, Mn)-Al LDHs or Ni-Fe LDH. H2 -O2 fuel cells with Ni-Al or Mg-Al LDHs as an electrolyte and MnO2 as the cathode catalyst were fabricated. The H2 -O2 fuel cells were confirmed to be operated.